Cytotoxic and proinflammatory effects of PVP-coated silver nanoparticles after intratracheal instillation in rats - Haberl, Nadine; Hirn, Stephanie; Wenk, Alexander; Diendorf, Jörg; Epple, Matthias; Johnston, Blair D.; Krombach, Fritz; Kreyling, Wolfgang G.; Schleh, Carsten (Beilstein Journal of Nanotechnology, 2013)
Silver nanoparticles (AgNP) are among the most promising nanomaterials, and their usage in medical applications and consumer products is growing rapidly. To evaluate possible adverse health effects, especially to the lungs, the current study focused on the cytotoxic and proinflammatory effects of AgNP after the intratracheal instillation in rats. Monodisperse, PVP-coated AgNP (70 nm) showing little agglomeration in aqueous suspension were instilled intratracheally. After 24 hours, the lungs were lavaged, and lactate dehydrogenase (LDH), total protein, and cytokine levels as well as total and differential cell counts were measured in the bronchoalveolar lavage fluid (BALF). Instillation of 50 µg PVP-AgNP did not result in elevated LDH, total protein, or cytokine levels in BALF compared to the control, whereas instillation of 250 µg PVP-AgNP caused a significant increase in LDH (1.9-fold) and total protein (1.3-fold) levels as well as in neutrophil numbers (60-fold) of BALF. Furthermore, while there was no change in BALF cytokine levels after the instillation of 50 µg PVP-AgNP, instillation of 250 µg PVP-AgNP resulted in significantly increased levels of seven out of eleven measured cytokines. These finding suggest that exposure to inhaled AgNP can induce moderate pulmonary toxicity, but only at rather high concentrations.
Keywords: cytotoxicity; inflammation; pulmonary toxicity; silver nanoparticles

(untitled) - Chernousova, S.; Epple, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Fichtner, J.; Güresir, E.; Seifert, V.; Raabe, A. (J. Neurosurg., 2010)

(untitled) - Pollini, M.; Paladini, F.; Catalano, M.; Taurino, A.; Licciulli, A.; Maffezzoli, A.; Sannino, A. (J. Mater. Sci.: Mater. Med., 2011)

(untitled) - Toy, L. W.; Macera, L. (J. Am. Acad. Nurse Pract., 2011)

(untitled) - Wiegand, C.; Heinze, T.; Hipler, U.-C. (Wound Repair Regen., 2009)

(untitled) - Edwards-Jones, V. (Lett. Appl. Microbiol., 2009)

(untitled) - Walser, T.; Demou, E.; Lang, D. J.; Hellweg, S. (Environ. Sci. Technol., 2011)

(untitled) - Foss Hansen, S.; Maynard, A.; Baun, A.; Tickner, J. A. (Nat. Nanotechnol., 2008)

(untitled) - Quadros, M. E.; Marr, L. C. (Environ. Sci. Technol., 2011)

Particle Toxicology - Kreyling, W. G.; Möller, W.; Semmler-Behnke, M.; Oberdörster, G. (CRC Press, Taylor & Francis Croup, 2007)

Nanomaterials – Toxicity, Health and Environmental Issues - Kreyling, W. G.; Semmler-Behnke, M.; Moeller, W. (Wiley-VCH, 2005)

(untitled) - Kreyling, W. G.; Semmler-Behnke, M.; Möller, W. (J. Aerosol Med., 2006)

(untitled) - Mühlfeld, C.; Rothen-Rutishauser, B.; Blank, F.; Vanhecke, D.; Ochs, M.; Gehr, P. (Am. J. Physiol., 2008)

(untitled) - Schleh, C.; Hohlfeld, J. M. (Inhalation Toxicol., 2009)

(untitled) - Schleh, C.; Mühlfeld, C.; Pulskamp, K.; Schmiedl, A.; Nassimi, M.; Lauenstein, H. D.; Braun, A.; Krug, N.; Erpenbeck, V. J.; Hohlfeld, J. M. (Respir. Res., 2009)

(untitled) - Geiser, M.; Kreyling, W. (Part. Fibre Toxicol., 2010)

(untitled) - Kreyling, W. G.; Semmler-Behnke, M.; Takenaka, S.; Möller, W. (Acc. Chem. Res., 2013)

(untitled) - Carlson, C.; Hussain, S. M.; Schrand, A. M.; Braydich-Stolle, L. K.; Hess, K. L.; Jones, R. L.; Schlager, J. J. (J. Phys. Chem. B, 2008)

(untitled) - AshaRani, P.; Low Kah, M.; Hande, M. P.; Valiyaveettil, S. (ACS Nano, 2009)

(untitled) - Stensberg, M. C.; Wei, Q.; McLamore, E. S.; Porterfield, D. M.; Wei, A.; Sepúlveda, M. S. (Nanomedicine, 2011)

(untitled) - Park, E.-J.; Choi, K.; Park, K. (Arch. Pharmacal Res., 2011)

(untitled) - Stebounova, L. V.; Adamcakova-Dodd, A.; Kim, J. S.; Park, H.; O'Shaughnessy, P. T.; Grassian, V. H.; Thorne, P. S. (Part. Fibre Toxicol., 2011)

(untitled) - Sung, J. H.; Ji, J. H.; Park, J. D.; Yoon, J. U.; Kim, D. S.; Jeon, K. S.; Song, M. Y.; Jeong, J.; Han, B. S.; Han, J. H.; Chung, Y. H.; Chang, H. K.; et al. (Toxicol. Sci., 2009)

(untitled) - Sung, J. H.; Ji, J. H.; Yoon, J. U.; Kim, D. S.; Song, M. Y.; Jeong, J.; Han, B. S.; Han, J. H.; Chung, Y. H.; Kim, J.; Kim, T. S.; Chang, H. K.; et al. (Inhalation Toxicol., 2008)

(untitled) - Ji, J. H.; Jung, J. H.; Kim, S. S.; Yoon, J. U.; Park, J. D.; Choi, B. S.; Chung, Y. H.; Kwon, I. H.; Jeong, J.; Han, B. S.; Shin, J. H.; Sung, J. H.; et al. (Inhalation Toxicol., 2007)

(untitled) - Sung, J. H.; Ji, J. H.; Song, K. S.; Lee, J. H.; Choi, K. H.; Lee, S. H.; Yu, I. J. (Toxicol. Ind. Health, 2011)

(untitled) - Liu, J.; Wang, Z.; Liu, F. D.; Kane, A. B.; Hurt, R. H. (ACS Nano, 2012)

(untitled) - Johnston, H. J.; Hutchison, G.; Christensen, F. M.; Peters, S.; Hankin, S.; Stone, V. (Crit. Rev. Toxicol., 2010)

(untitled) - Müller, L.; Gasser, M.; Raemy, D. O.; Herzog, F.; Brandenberger, C.; Schmid, O.; Gehr, P.; Rothen-Rutishauser, B.; Clift, M. J. (Insci. J., 2011)

(untitled) - Greulich, C.; Diendorf, J.; Geßmann, J.; Simon, T.; Habijan, T.; Eggeler, G.; Schildhauer, T. A.; Epple, M.; Köller, M. (Acta Biomater., 2011)

(untitled) - Greulich, C.; Diendorf, J.; Simon, T.; Eggeler, G.; Epple, M.; Köller, M. (Acta Biomater., 2010)

(untitled) - Park, J.; Lim, D.-H.; Lim, H.-J.; Kwon, T.; Choi, J.-s.; Jeong, S.; Choi, I.-H.; Cheon, J. (Chem. Commun., 2011)

(untitled) - Kim, S.; Choi, I.-H. (Yonsei Med. J., 2012)

(untitled) - AshaRani, P. V.; Sethu, S.; Lim, H. K.; Balaji, G.; Valiyaveettil, S.; Hande, M. P. (Genome Integr., 2012)

(untitled) - Stone, K. C.; Mercer, R. R.; Gehr, P.; Stockstill, B.; Crapo, J. D. (Am. J. Respir. Cell Mol. Biol., 1992)

(untitled) - Tran, C. L.; Buchanan, D.; Cullen, R. T.; Searl, A.; Jones, A. D.; Donaldson, K. (Inhalation Toxicol., 2000)

(untitled) - Kittler, S.; Greulich, C.; Diendorf, J.; Köller, M.; Epple, M. (Chem. Mater., 2010)

(untitled) - Kreyling, W. G. (J. Aerosol Sci., 1990)

(untitled) - Tejamaya, M.; Römer, I.; Merrifield, R. C.; Lead, J. R. (Environ. Sci. Technol., 2012)

(untitled) - Bryaskova, R.; Pencheva, D.; Nikolov, S.; Kantardjiev, T. (J. Chem. Biol., 2011)

(untitled) - El Badawy, A. M.; Silva, R. G.; Morris, B.; Scheckel, K. G.; Suidan, M. T.; Tolaymat, T. M. (Environ. Sci. Technol., 2011)

(untitled) - Bilberg, K.; Hovgaard, M. B.; Besenbacher, F.; Baatrup, E. (J. Toxicol., 2012)

(untitled) - George, S.; Lin, S.; Ji, Z.; Thomas, C. R.; Li, L.; Mecklenburg, M.; Meng, H.; Wang, X.; Zhang, H.; Xia, T.; Hohman, J. N.; Lin, S.; et al. (ACS Nano, 2012)

(untitled) - Greulich, C.; Kittler, S.; Epple, M.; Muhr, G.; Köller, M. (Langenbeck's Archives of Surgery, 2009)

(untitled) - Wang, H.; Qiao, X.; Chen, J.; Ding, S. (Colloids Surf., A, 2005)